Precision measurement and symmetry properties of metastable hydrogen - Rasor, Cory M., author; Yost, Dylan, advisor; Roberts, Jacob, committee member; Mooney, Michael, committee member; Bartels, Randy, committee member (Colorado State University. Libraries, 2022)
Hydrogen has been an indispensable system to study during the development of quantum mechanics due to the simplicity of its atomic structure. Hydrogen maintains its utility today as an important tool for determining fundamental values such as the Rydberg and fine structure constants, as well as the proton charge radius. The work described in this thesis aims to use hydrogen for determining the proton Zemach radius, to search for anomalous spin-dependent forces, and to provide means for measuring the degree of parity violation within this simple system. An overview of a 2S1/2 hyperfine interval measurement is described, followed by a description of the apparatus used and finally a discussion of the systematic effects to be characterized. A proposed parity violation experiment is also described.
Keywords: parity; hydrogen; spectroscopy